Adipose-derived stem cells alleviate acute pancreatitis by inhibiting ferroptosis and oxidative damage in canines - Yansong Ge; Mingzhen Chen; Meilin Li; Zheng Wang; Ruxin Ding; Zhiying Wan; Enshuang Xu; Jiasan Zheng (Stem Cell Research & Therapy)
Abstract Background Acute pancreatitis (AP) is a common exocrine pancreatic disease that can lead to systemic inflammatory response syndrome and multiorgan failure in canines. The therapeutic benefits of adipose-derived stem cells (ADSCs) and conditioned medium (CM) and the role in ferroptosis regulation in managing AP in canines (dogs) were investigated in this study. Methods Sixteen dogs were randomly divided into a control (CON), AP, ADSC, or ADSC-CM group. The AP model was established by injecting the dogs with sodium taurocholate (5%, 0.1 mL/kg) and trypsin (3500 U/kg) via the pancreaticobiliary duct. ADSCs (1 × 106/kg) and CM (0.1 mL/kg) were injected intravenously 6 h after surgery, and the roles on ferroptosis and oxidative stress were analyzed. The changing patterns of ferroptosis and oxidative stress were determined in vitro using a lipopolysaccharideinduced cellular inflammation model of AR42J. Results Ferroptosis occurred in the pancreas during AP, as evidenced by significant iron accumulation, suppressed glutathione peroxidase (GPx)4 expression, and increased transferrin receptor-1 (TFR1), and ferritin heavy chain expression. Treatment with ADSCs and ADSC-CM led to pathological remission and effectively restored abnormal amylase and lipase levels. ADSC-CM showed ferroptosis-alleviating effects similar to that of ADSCs, with reduced iron accumulation and increased GPx4 expression. Furthermore, ADSCs could promote the nuclear translocation of nuclear factor erythroid 2–related factor 2 and initiate the transcription of detoxification enzymes to protect the pancreas from oxidative damage. Conclusions ADSCs can protect the pancreas of dogs by inhibiting ferroptosis and oxidative stress via paracrine function, indicating immense potential as a therapeutic target for treating AP.